Analisis Finansial Hutan Rakyat Pola Agroforestri Herbal di Desa Gerbosari Kabupaten Kulon Progo - Hafizah Arinah; Wahyu Andayani; Ris Hadi Purwanto (Jurnal Ilmu Kehutanan, 2021)
This research aimed to assess the feasibility of herb agroforestry utilization in the community forest of Gerbosari Village, Kulon Progo. This research measured NPV (Net Present Value), Net B/C (Net Benefit-Cost Ratio), IRR (Internal Rate of Return), and AEV (Annual Equivalent Value) as the financial feasibility criteria. A stratified sampling method was employed in which sixty farmers were classified into three strata based on the size of their lands. Based on the financial feasibility analysis, in stratum I, the values of the criteria measured were NPV of IDR15,757,980.56/ha/25 years, Net B/C of 1.62, IRR of 22.12%, and AEV of IDR1,296,647.20/year. In stratum II, the values of criteria measured were NPV of IDR14,255,408.39/ha/25 years, Net B/C of 1.76, IRR of 23.78%, and AEV of IDR1,173,007.88/year. Finally, in stratum III, the criteria measured were NPV of IDR19,444,703.86/ha/25 years, Net B/C of 2.21, IRR of 32%, and AEV of IDR1,600,009.64/year. The results suggest that herb agroforestry plays an important role in farmers' livelihood particularly as a source of income in both the short and long terms. The herb agroforestry utilization contributes positively to the economy of Gerbosari Village, Kulon Progo District.